1994
DOI: 10.1177/00220345940730031401
|View full text |Cite
|
Sign up to set email alerts
|

Potential Efficacy of Chlorhexidine against Mutans Streptococci and Human Dental Caries

Abstract: Chemotherapeutic agents have been considered as having potential for the prevention of dental caries. Several substances have been evaluated as possible candidates, but no antimicrobial agent, with the exception of fluoride, has received as much experimental attention as the bisbiguanide chlorhexidine. This substance represents, so far, the most effective and best-documented agent. To be effective against caries, therapeutic dosages of the antimicrobial agent have to be given for a sufficient but finite time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
179
4
10

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(205 citation statements)
references
References 78 publications
(98 reference statements)
12
179
4
10
Order By: Relevance
“…The antibacterial effect of fluoride in the concentrations remaining in the oral cavity, predominantly below 10 ppm, cannot affect bacterial metabolism. 10 Also, once a great mineral loss has occurred, and the clinical signs are already visible (e.g. a white spot lesion), fluoride is not able to replenish the porous area inside the enamel with minerals, but will help impair the process, resulting in the arrestment of the caries lesion progression.…”
Section: Strengths and Limitations Of Fluoride Mechanisms To Control mentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial effect of fluoride in the concentrations remaining in the oral cavity, predominantly below 10 ppm, cannot affect bacterial metabolism. 10 Also, once a great mineral loss has occurred, and the clinical signs are already visible (e.g. a white spot lesion), fluoride is not able to replenish the porous area inside the enamel with minerals, but will help impair the process, resulting in the arrestment of the caries lesion progression.…”
Section: Strengths and Limitations Of Fluoride Mechanisms To Control mentioning
confidence: 99%
“…Such concepts as "fluoride strengthening teeth", "increasing the resistance of teeth to acids" and "reducing the acid produced by bacteria", although theoretically reasonable, are no longer accepted as clinically relevant to the reduction of caries associated with fluoride use. 7,10 In other words, fluoride is not able to affect biofilm accumulation (necessary factor) and the production of acids from its exposure to sugars (determinant factor), but will chemically reduce the mineral loss induced by the combination of these two factors, through the precipitation of a fluoridated mineral on teeth. How to maximize this effect, by using fluoride from different methods of delivery, will be the focus of the next sections in this paper.…”
mentioning
confidence: 99%
“…With regard to oral biofilm models, chlorhexidine has been used as the 'gold standard' because it is considered the most efficient topical substance to reduce dental plaque, a type of biofilm. 16 Moreover, it is recognized that although fluoride is the most important anticaries substance, 17 its antibacterial effect is limited 18 and the model should simulate the main mechanism of action of fluoride on dental caries.…”
Section: Introductionmentioning
confidence: 99%
“…The most accepted explanation for its lower effect on MS and their consequent reappearance is the recolonization of the microorganisms, probably because the reservoirs and retention sites in the dentition are not sufficiently reached due to the low bioavailability of CHX [12]. Clinical studies show that after a treatment with CHX there is an initial decrease in the presence of MS, but after some time the ecological conditions of the environment favor the recolonization of the dental surfaces by these microrganisms, which may have occurred in this study [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride has an important effect on the inhibition of demineralization and on activating the remineralization of tooth structures. Chlorhexidine is able to act on the bacterial metabolism and suppress the growth of total microorganisms and mutans streptococci [11,12]. Moreover, some studies have demonstrated that CHX could also inhibit the activity of dentine matrix metalloproteinases (MMPs) [13], suggesting that it could help to prevent dentine demineralization [14].…”
Section: Introductionmentioning
confidence: 99%